2015
DOI: 10.2174/1567205012666150530203214
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI Predictors of Late-Life Cognition Differ Across African Americans, Hispanics, and Whites

Abstract: Background Structural magnetic resonance imaging (MRI) provides key biomarkers to predict onset and track progression of Alzheimer’s disease (AD). However, most published reports of relationships between MRI variables and cognition in older adults include racially, ethnically, and socioeconomically homogenous samples. Racial/ethnic differences in MRI variables and cognitive performance, as well as health, socioeconomic status and psychological factors, raise the possibility that brain-behavior relationships ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 33 publications
8
91
5
Order By: Relevance
“…Our results, however, point to a significant decline in volumes and increasing atrophy of the HP and the EC from CN state to dementia, in both Hispanics and WNHs, as in accordance with previous reports (DeCarli et al, 2008; Loewenstein et al, 2009; Zahonde et al, 2015). Enlargement of an inferior lateral ventricle indicates atrophy in the regions surrounding this structure, including the HP, parahippocampal gyrus, lingual and inferior temporal gyri, amygdala, and related white matter structures.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results, however, point to a significant decline in volumes and increasing atrophy of the HP and the EC from CN state to dementia, in both Hispanics and WNHs, as in accordance with previous reports (DeCarli et al, 2008; Loewenstein et al, 2009; Zahonde et al, 2015). Enlargement of an inferior lateral ventricle indicates atrophy in the regions surrounding this structure, including the HP, parahippocampal gyrus, lingual and inferior temporal gyri, amygdala, and related white matter structures.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings of equivalent or better cognitive scores on Digit Span Forward and Category Fluency test among WNH, than among Hispanics, despite greater severity of overall neuro-degeneration, suggests that language and cultural factors may provide an advantage to WNHs. Similar findings were reported previously by Mungas, Reed, Farias, and DeCarli (2009) and Zahodne et al (2015), who found that HPCv was larger among Hispanics than in WNHs, whereas WNHs scored better on memory and non-memory measures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, in the arena of cognitive assessment neuropsychological test findings may now be explored in relation to neuroimaging defined anatomical and pathological correlates for all conditions and disorders. Traditionally neuropsychological tasks have been divided into the customary areas of motor, sensory-perceptual, language, visuospatial, speed of processing/executive functioning and emotional control when compared to neuroimaging findings (see Zahodne et al 2015). Using these different neuropsychological domains a brief overview of contemporary findings mainly using the T1-weighted FreeSurfer technique is provided below.…”
Section: Contemporary Examples Of Structural Neuroimaging Findings Inmentioning
confidence: 99%